DEMAND FUNCTION FOR MEAT IN BENGHAZI - S. MUKERJI , S. MUKERJI (Dirasat in Economics and Business, 1969)
In an earlier paper, seasonal movement in the consumption of meat in Renehazi 1 was discussed. In this paper demand function for the Three varieties of meat will be discussed. The three varieties of meat considered are of lamb, calf and camel. Use of demand function in market analysis is well known 2. However, derivation of demand function from observed data presents some serious difficulties. Usually mutiple regression analysis is used for estimating the demand equation. The dependent variable being the quantity exchanged in the market, independent variables are the price, prices of related commodities and income. Price of the commodity and prices of related commodities are likely to be strongly correlated. This is called the problem of multicollinearity. Presence of multicollinearity may not, under other conditions on the residuals, discredit the estima. ted demand equation for the purpose of prediction but it is likely to influence adversely the estimated regression coefficients by increasing the errors in the estimates. Fortunately, in the data the important determining variables namely, price of lamb meat, price of beef and price of camel meat do not show strong correlation. An interesting point arises here ; from the data it can be seen that the total correlation coefficient between price of lamb meat and beef or between price of (*) S. Mukerji, M.Sc., M.Sc., Ph.D. is on the teaching staff of the Economics and Commerce, University of Libya, Benghazi. (1) Mukerji Et - al. The Libyan Economic and Business Review, Vol. V no. 1 Spring 1969. (2) O. Lange: Econometrics. 26 THE LIBYAN ECONOMIC AND BUSINESS REVIEW large because each vation lainb meat and camel or between price of beef and camel meat i dually is not small. But these correlations are large because price series shows similar variation over the period of observa Thus the apparent correlation is misleading and in fact the prices The three varieties of meat are uncorrelated when the effect of time held constant. This point will be further discussed later in the to of ne is The data gave the number of lambs, calves and camels each month butchered in the Benghazi municipal slaughtering house between the period July 1963 to June 1968. For lamb meat the market had two varieties, namely, local and imported. For beef and camel meat again two varieties of each were available, those from big animals and those from smaller animals. Price of each variety, each month, was quoted as interval. Mid. values of the interval was taken as the price of each month. For each type of meat a weighted average price per month was calculated. For the months of February, March and April each year, 50 per cent of the lambs butchered were assumed to be local, the remaining 50 per cent imported. For other months, each year, it was assumed that 75 percent of the lambs were imported variety and the remaining 25 per cent local lamb. For calves and camels it was assumed that each month 70 per cent of the animals butchered were big and the remaining 30 per cent were from smaller animals. These assumptions are based on the suggestions made by the authorities in the slaughtering house and the people actually doing the work. Table 1 shows the number of animals of each variety and the weighted average price of meat per kilogram. Methodology : Demand equation of a commodity is usually taken as q = a-bp + c p + dI, where q is the quantity, p the price of the commodity, p the price or prices of related commodity and I the income of the consumers. Unfortunately the distribution of household income in Benghazi is not known. Without a detailed family budget survey it